Approximation by max-product operators of Kantorovich type: Dedicated to Professor Heiner Gonska on the occasion of his 70th anniversary. - COROIANU, Lucian; GAL, Sorin G. (Studia Universitatis Babeș-Bolyai Mathematica, 2019)
We associate to various linear Kantorovich type approximation operators, nonlinear max-product operators for which we obtain quantitative approximation results in the uniform norm, shape preserving properties and localization results. Mathematics Subject Classification (2010): 41A35, 41A25, 41A20.